Kinetic Modeling of Electromembrane Extraction of Copper using a Novel Electrolytic Cell Provided with a Supported Liquid Membrane - Kadhim, Noor R.; Flayeh, Hussain M.; Abbar, Ali H. (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The aim of this study is to investigate the kinetics of copper removal from aqueous solutions using an electromembrane extraction (EME) system. To achieve this, a unique electrochemical cell design was adopted comprising two glass chambers, a supported liquid membrane (SLM), a graphite anode, and a stainless-steel cathode. The SLM consisted of a polypropylene flat membrane infused with 1-octanol as a solvent and bis(2-ethylhexyl) phosphate (DEHP) as a carrier. The impact of various factors on the kinetics constant rate was outlined, including the applied voltage, initial pH of the donor phase solution, and initial copper concentration. The results demonstrated a significant influence of the applied voltage on enhancing the rate of copper mass transfer across the membrane. As the applied voltage increased, the rate constant also increased. Additionally, increasing the pH of the solution led to an initial elevate in the rate constant, reaching a maximum value at pH 5, after which it started to decline. Moreover, higher initial copper concentrations had an adverse effect on the rate constant. Notably, the concentration decay profiles observed under different operating conditions followed first-order kinetics, with correlation coefficients exceeding 0.99. The elucidation of this discovery emanated from a remarkable and striking congruence between the experimental data and the mathematical underpinnings of the first-order kinetics model. This serendipitous alignment profoundly reinforced the robustness, veracity, and unwavering reliability of meticulously obtained results, amplifying the credibility and trustworthiness of the present comprehensive study.